2021
DOI: 10.3390/metabo11100708
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics Reveals Heterogeneity in the Chemical Composition of Green and White Spears of Asparagus (A. officinalis)

Abstract: Green and white asparagus are quite different crops but can be harvested from the same plant. They have distinct morphological differences due to their mode of cultivation and they are characterised by having contrasting appearance and flavour. Significant chemical differences are therefore expected. Spears from three varieties of both green and white forms, harvested in two consecutive seasons were analysed using headspace GC-MS and LC-MS with an untargeted metabolomic workflow. Mainly C5 and C8 alcohols and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 58 publications
1
16
0
Order By: Relevance
“…These aldehydes have been identified in asparagus. Among these, benzeneacetaldehyde, octanal, and 3-methylbutanal are regarded as vegetable VOCs, and their aroma are associated with floral, fruity, and fresh [ 8 , 34 ]. These two acids were first reported in asparagus.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These aldehydes have been identified in asparagus. Among these, benzeneacetaldehyde, octanal, and 3-methylbutanal are regarded as vegetable VOCs, and their aroma are associated with floral, fruity, and fresh [ 8 , 34 ]. These two acids were first reported in asparagus.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, studies have reported on the metabolic profiles of asparagus, revealing differences in metabolomics between green and white spears of asparagus. Green spears mainly contained aldehydes and phenols, whereas white spears mainly contained benzenes, steroidal saponins, and unsaturated aldehydes [ 8 ]. The main differences in taste are that green asparagus is grassy and bitter, whereas white asparagus is similar to sweet corn, potatoes, and butter [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different environments lead to the development of different plant traits, which can also be transformed into variations in metabolomes ( Pegiou et al, 2021 ). For example, Lee et al (2013) analyzed the effect of shade treatment on the nutritional and sensory qualities of green tea using metabolomics technology.…”
Section: Discussionmentioning
confidence: 99%
“…The semipolar compounds were extracted by mixing 0.3mL of each soup replicate with 0.9mL 32.04M methanol and 0.035M formic acid followed by sonication and centrifugation, as described previously by De Vos et al ( 2007). The LC-MS calibration and analysis settings were as previously described (Pegiou et al, 2021) using both negative and positive ionization modes of the Q Exactive™ Plus Hybrid Quadrupole-Orbitrap™ Mass Spectrometer (Thermos Fisher Scientific™, Germany). A 0.3mL from the same mixture of all samples as prepared and mentioned in 6.2.6, was used for each QC sample and analysed in the same way as the biological samples.…”
Section: Analysis Of Non-volatile Compoundsmentioning
confidence: 99%